Incorporation of gamma linolenic acid with sodium carboxymethyl cellulose using surfactant system in thin film preparation / Siti Nazila Ishak - Ishak, Siti Nazila (2015)
This study was done to develop an optimized film formulation of GLA with SCMC usmg surfactant system. Thin films offer more dosage flexibility and ease of use, less irritation potential, better cosmetic appearance, higher simplicity of manufacture, and longer duration of drug release. GLA is an essential fatty acid and currently being used by dermatologists to treat skin problem such as atopic dermatitis, acne, psoriasis and rheumatoid arthritis. Sodium carboxymethyl cellulose (SCMC) is a cellulose type polymer derivative and commonly acts as a water soluble polymer in thin film preparation. Incorporation of 2.5% (w/w) GLA with 1.5% (w/w) to 2% (w/w) SCMC in a thin film preparation by solvent casting method. Several thin films were prepared by a single or combination of surfactant: PVP, Tween 80 and lecithin, in order to investigate the relationship between the surfactant system and physical properties of thin film. The mechanical properties and surface morphology also was determined by using texture analyser and SEM respectively. Film 8 that was formulated by incorporating of 2.5% GLA with 1.5% SCMC and 3% PVP has a good physical and mechanical properties, also appear smooth and even surface under SEM examination.